Measuring the success of employee engagement : a step-by-step guide for measuring impact and calculating ROI - Phillips, Patricia Pulliam; Phillips, Jack J., 1945-; Ray, Rebecca (ATD Press, 2016)
Helping you make the business case for an employee engagement initiative, this book presents real case studies you can follow that show the authors' ROI Methodology in action, and explains how to avoid narrowly focusing your efforts on behavioral outcomes alone. --